Pengelolaan laboratorium produksi mesin CNC berbasis microsoft visual basic 6.0 di Politeknik Negeri Banjarmasin - Roby Cahyadi; Arifin (LPPM Politeknik Jambi, 2019)
Every company wants all its equipment or machinery operating in optimum condition, so that the necessary maintenance activities to fulfill that desire. Management of maintenance activities to be hard to do when the equipment or machines owned by increasingly numerous and complex, and activities increase the number of machines or equipment routinely performed. Therefore needed a system to manage maintenance activities quickly, especially in administration of maintenance of machine or equipment are handled. This program has the ability to manage personal data engines, machinery or equipment maintenance scheduling, managing work instruction sheet, a history of the machine, the data parts, data managing maintenance activities, Preventive maintenance and expense reports. System maintenance is made by using a computer-based information system maintenance. In making the program used Microsoft Visual Basic 6.0 and used for the purpose of Microsoft Access database.